DNA Binding Studies of Ternary Copper (II) Complexes of Doxycycline with Polypridyl Ligands - Obaleye, Joshua A.; Abosede, Olufunso O. (International Journal of Environment, Agriculture and Biotechnology, 2019)
Tetracyclines are a family of drugs with interesting pleiotropic properties. The recognition by scientists of the therapeutic properties and safety profile of this class of drugs has led to the continuous derivatization of these compounds and implementation of clinical trials to explore their potential applications for a wide range of diseases. To this end, this paper review literature on tetracyclines from the discovery of the first tetracycline to a new class of tetracyclines called glycylcyclines. The DNA binding propensities of some copper (II) complex of doxycycline and mixed ligand copper (II) doxycycline complexes with polypyridyl ligands were also investigated by UV-Vis titration, viscosity and thermal melting experiments. The mixed ligand copper (II) doxycycline complexes with polypyridyl ligands were found to bind CT DNA in the major groove in a similar fashion to methyl green causing no change in the viscosity and negligible increase in thermal melting of CT DNA.